Social norms, attitudes and access to modern contraception for adolescent girls in six districts in Uganda - Paul Bukuluki; Peter Kisaakye; Maxime Houinato; Adekemi Ndieli; Evelyn Letiyo; Dan Bazira (BMC, 2021)
Abstract Background Social norms continue to be entrenched in Uganda. Understanding social norms helps to uncover the underlying drivers that influence attitudes and behavior towards contraceptive access and use. This study therefore seeks to investigate the factors that influence the social norm - access to contraception by adolescent girls - in six districts in Uganda. Data and methods: Using data from a community cross-sectional survey in six districts (Amudat, Kaberamaido, Kasese, Moroto, Tororo and Pader) in Uganda, a binary logistic regression model was fitted to examine the variation in individual beliefs and socio-economic and demographic factors on 'allowing adolescent girls to access contraception in a community' - we refer to as a social norm. Results Results demonstrate that a higher proportion of respondents hold social norms that inhibit adolescent girls from accessing contraception in the community. After controlling for all variables, the likelihood for adolescent girls to be allowed access to contraception in the community was higher among respondents living in Kaberamaido (OR = 2.58; 95 %CI = 1.23-5.39), Kasese (OR = 2.62; 95 %CI = 1.25-5.47), Pader (OR = 4.35; 95 %CI = 2.15-8.79) and Tororo (OR = 9.44; 95 %CI = 4.59-19.37), those aged 30-34 years likely (OR = 1.73; 95 %CI = 1.03-2.91). However, the likelihood for respondents living in Moroto to agree that adolescent girls are allowed to access contraception was lower (OR = 0.27; 95 %CI = 0.11-0.68) compared to respondents living in Amudat. Respondents who were not formally employed (OR = 0.63; 95 %CI = 0.43-0.91), and those who agreed that withdrawal prevents pregnancy (OR = 0.45; 95 %CI = 0.35-0.57) were less likely to agree that adolescent girls are allowed to access contraception in the community. Respondents who agreed that a girl who is sexually active can use contraception to prevent unwanted pregnancy (OR = 1.84; 95 %CI = 1.33-2.53), unmarried women or girls should have access to contraception (OR = 2.15; 95 %CI = 1.61-2.88), married women or girls should have access to contraception (OR = 1.55; 95 %CI = 0.99-2.39) and women know where to obtain contraception for prevention against pregnancy (OR = 2.35; 95 %CI = 1.19-4.65) were more likely to agree that adolescent girls are allowed to access contraception. Conclusions The findings underscore the need for context specific ASRH programs that take into account the differences in attitudes and social norms that affect access and use of contraception by adolescents.